Perbedaan Gaya Belajar Anak Laki-Laki dan Perempuan Pada Mata Pelajaran PAI di SMP Negeri 2 Kota Bengkulu - Fitri Yanti; Alimni Alimni (UIN Fatmawati Sukarno Bengkulu, Indonesia, 2023)
This study aims to determine whether there are differences in the learning styles of male and female students in learning Islamic Religious Education at SMP Negeri 2 Kota Bengkulu, in the 2022/2023 academic year. This type of research is comparative research. The data collection technique uses questionnaires with Likert scales. Hypothesis testing using the Way Anova test. The results showed that: 1) grade VIII students in PAI lessons tended to learn with auditory style, which was 71,29%. 2) Male students of grade VIII tend to learn with visual style, which is 911.7%. 3) Female students in grade VIII tend to learn with auditory style by 174%. 4) there is a significant difference between the learning styles of grade VIII male and female students in PAI lessons, where male students are more inclined to visual styles (p: 01.036) while female students are more inclined to auditory styles (p: 01.001).